Finance in Africa for green, smart and inclusive private sector development - European Investment Bank (European Investment Bank, 2021)
Africa's recovery from the COVID-19 crisis will depend on private firms sustaining and creating jobs. But even previously thriving enterprises have been badly hit by the crisis. This report outlines the consequences of the health crisis in Africa, the potential cost of the recovery and the willingness of banks to support green investments as they look to the future.